The Image of an Architect and Masonic Symbols in Works by Milorad Pavić - Huk, Zoriana (Respectus Philologicus, 2021)
The paper analyzes works by the Serbian postmodernist writer Milorad Pavić. It attempts to prove that he possesses knowledge of royal art and uses masonic symbols in his writing related to geometry and architecture, including the radiant delta, compass, masonic gloves, and clepsydra. It is assumed that under the influence of these particular ideas, the writer creates the leading image of an architect and the motif of construction as freemasons believe in the Great Architect of the Universe. In the short novel Damascene, according to speculative masonry’s beliefs, the building of the church projects the building of a temple in a human soul. M. Pavić, as an architect, creates a structure of every novel, which he identifies with the golden section. This paper finds special symbols of the divine proportion in his prose, including snail’s shells, pyramids, and violins. A dynamic structure as an embodiment of the open work concept and a broad spectrum of themes provide artistic communication with a creative recipient. A reader has an opportunity to choose their own style of reading and solving textual puzzles because Pavić’s prose represents a wide variety of themes, symbols, images, and allusions that embody the secrets of Freemasonry, allowing for various interpretations.